2016
DOI: 10.1016/j.rbr.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

O volume plaquetário médio está reduzido em adultos com lúpus ativo

Abstract: In summary, MPV is decreased in adult patients with active lupus disease, and positively correlated with albumin, another biomarker of disease activity. Prospective studies are needed to evaluate the prognostic value of this biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Other studies have found results similar to ours [ 13 , 15 , 19 ]. In rheumatoid arthritis, there is a study that also demonstrated diminished results of MPV in the active disease.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Other studies have found results similar to ours [ 13 , 15 , 19 ]. In rheumatoid arthritis, there is a study that also demonstrated diminished results of MPV in the active disease.…”
Section: Discussionsupporting
confidence: 92%
“…MPV has been considered a possible marker of platelet activation and inflammatory process [ 13 ]. The pathophysiology of SLE involves the presence of inflammatory cytokines and deregulation of the complement system, which interferes with the activation of platelets [ 15 ]. A probable mechanism that may explain the relationship between reduced MPV and disease activity is the consumption of large platelets at sites of inflammation [ 6 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps the worst aspect of diabetes is the systemic inflammation and oxidative stress and they are almost accused of being the real reasons underlying many complications of diabetes [14] [15] [16]. MPV is now well known as a predictor of inflammation and has been shown in many cases as a marker of inflammation [17] [18] [19]. In our previous research, we have shown that we can use MPV in the diagnosis of uveitis and venous thrombosis in patients with Behçet's syndrome [20] [21].…”
Section: Introductionmentioning
confidence: 99%